Self-Administered Screening for Mild Cognitive Impairment: Initial Validation of a Computerized Test Battery - Tornatore, Jane B. (2005)
The CANS-MCI, a computer administered, scored, and interpreted touch screen battery, was evaluated for its ability to screen for mild cognitive impairment. 310 community-dwelling elders enrolled in an NIA-funded study. One-month test-retest reliability correlations were all significant (p<.05-p<.001). Concurrent validity correlations were all significant (p<.001). A high level of diagnostic validity was attained relative to the WMS-R LMS-II test (p<.001). Confirmatory factor analysis supported a three-factor model indicating the tests measure the intended cognitive dimensions of Memory, Language/Spatial Fluency, and Executive Function/Mental Control. Goodness of fit indicators were strong (Bentler Comparative Fit Index = .99; Root Mean Square Error of Approximation=.055). Initial validation analyses indicate that the CANS-MCI shows promise of being a reliable, valid screening tool to determine whether more intensive testing for early cognitive impairment is warranted.